A Buffer Stock Model to Ensure Price Stabilization and Availability of Seasonal Staple Foods under Free Trade Considerations - Wahyudi Sutopo; Senator Nur Bahagia; Andi Cakravastia; T.M.A. Arisamadhi (Journal of Engineering and Technological Sciences, 2012)
Price  volatility  and  scarcity  have  become  a  great  problem  in  the distribution  system  of  seasonal  staple  foods  produced  by  the  agricultural industry.  There  is  a  salient  supply  disparity  during  the  harvest  and  planting seasons.  This  condition  could  cause  disadvantages  to  stakeholders  such  as producers,  wholesalers,  consumers,  and  government.  This  paper  proposes  a buffer  stock  model  under  free-trade  considerations  to  substitute  quantitative restrictions  and  tariffs  with  an  indirect  market  intervention   instrument.  This instrument  was  developed  using  a  buffer  stock  scheme  in  accordance  with  a  warehouse receipt system  (WRS) and  a  collateral management system.  A  public service  institution  for  staple  food  buffer  stock   (BLUPP)  is  proposed  as  the wholesaler's competitor,  with  as main responsibility   to ensure price stabilization and availability of staple food. Multi-criteria decision-making is formulated as a single  objective  mixed  integer  non-linear  programming  (MINLP)  model.  The results  shows  that  the  proposed  model  can  be  applied  to  solve  the  distribution problem  and  can  give  more  promising  outcomes  than  its  counterpart,  direct market intervention.